2019
DOI: 10.1002/qute.201900013
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Quantum Computation with Shortcuts to Adiabaticity

Abstract: Realization of a large-scale quantum computation relies on fast and high-fidelity quantum control. Geometric quantum control is thought to be a promising candidate for quantum computation which consolidates the robustness against both random noise (through the global geometrical feature) and systematic errors (through adiabatic characteristic). The adiabatic process of geometric control can be accelerated through an auxiliary Hamiltonian in different scenarios by means of shortcuts to adiabaticity (STA). Espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 129 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…Therefore, NHQC can reduce the influence of decoherence to the unitary operations by shortening the operation time. In addition, recent works [33][34][35][36][37] have indicated that NHQC is compatible with a lot of control and optimal methods, such as reverse engineering [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and the systematic-error-sensitivity nullified optimal control method [55][56][57][58][59][60]. By using proper control methods in NHQC, robustness against systematic errors can be significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NHQC can reduce the influence of decoherence to the unitary operations by shortening the operation time. In addition, recent works [33][34][35][36][37] have indicated that NHQC is compatible with a lot of control and optimal methods, such as reverse engineering [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and the systematic-error-sensitivity nullified optimal control method [55][56][57][58][59][60]. By using proper control methods in NHQC, robustness against systematic errors can be significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…They offer alternative fast and accurate processes which can reproduce the same final populations, or even the same final state in a shorter time, compared to the adiabatic evolution [8,9]. Recently, STA have been widely used to implement rapid and robust quantum information processing in theory, such as quantum state transfer [10][11][12][13][14][15][16], quantum gates [17][18][19][20][21][22][23][24], and generation of quantum cat state [25][26][27], etc. For instance, in 2012, Chen et al [11] used the invariantbased shortcut to accelerate the STIRAP to realize population transfers in a short time.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum computation has been shown to be more efficient than classical one in solving some problems, such as factoring large integers, searching big database and finding optimal solutions by quantum annealing [1]. However, it still faces great challenges both in theory and applications, especially, due to the inevitable decoherence or noise introduced by the interaction with environment, which destroys the coherence of the state which should be maintained in the parallel computation.…”
Section: Introductionmentioning
confidence: 99%